The Influence of Agile Management Processes on Risk Management and Performance: Case UAE Construction Sector - BAATHMAN, SAID (2023)
With the rapid and dynamic nature of construction projects in recent years, risk management has become highly important to navigate through the uncertainties that come with construction projects. however, the traditional approach has not been keeping up with these changes, and that can be noticed from the performance of the construction projects in recent years since cost and time overrun have been recurring problems in the construction sector. Agile management has risen in the IT sector as a substitute for traditional management, to introduce flexibility to the project and enhance the delivery of the project. The purpose of this paper is to study the influence of agile management processes on risk management and project performance of construction projects in the UAE. To understand the implications of agile management on risk management and project performance in construction projects, a number of online interviews have been conducted to assess agile management principles' impact on risk management. The interview responses have all agreed to the positive influence of agile management on risk management and project performance. after analyzing the data, a framework has been proposed consisting of agile determinants to address and manage risks and enhance construction project performance.